Fundamentals and Applications of Metasurfaces. Issue 4 (24th March 2017) - Hsiao, Hui‐Hsin; Chu, Cheng Hung; Tsai, Din Ping
Abstract : Metasurfaces have become a rapidly growing field of research in recent years due to their exceptional abilities in light manipulation and versatility in ultrathin optical applications. They also significantly benefit from their simplified fabrication process compared to metamaterials and are promising for integration with on‐chip nanophotonic devices owing to their planar profiles. The recent progress in metasurfaces is reviewed and they are classified into six categories according to their underlying physics for realizing full 2π phase manipulation. Starting from multi‐resonance and gap‐plasmon metasurfaces that rely on the geometric effect of plasmonic nanoantennas, Pancharatnam–Berry‐phase metasurfaces, on the other hand, use identical nanoantennas with varying rotation angles. The recent development of Huygens' metasurfaces and all‐dielectric metasurfaces especially benefit from highly efficient transmission applications. An overview of state‐of‐the‐art fabrication technologies is introduced, ranging from the commonly used processes such as electron beam and focused‐ion‐beam lithography to some emerging techniques, such as self‐assembly and nanoimprint lithography. A variety of functional materials incorporated to reconfigurable or tunable metasurfaces is also presented. Finally, a few of the current intriguing metasurface‐based applications are discussed, and opinions on future prospects are provided. Abstract : Metasurfaces as two‐dimensional analogs of metamaterials are highly feasible for the realization of exceptional abilities for light molding beyond that offered by conventional planar interfaces. An overview of recent progress on metasurfaces from their fundamental theoretical background, physical realization, and fabrication, to potential practical applications such as wave plates, polarimetries, metalenses, metaholograms, and optical vortex converters is presented.